Computing in Fish Schools: A Model Based on Shoaling Fish Suggests How a Group Can Show Decision-Making Properties Beyond Those of Any One Individual - Ispolatov, y (eLife Sciences Publications Ltd, 2016)
Sin Resumen Disponible